Antiviral activity of different extracts of standardized propolis preparations against HSV - Demir, Sevda; Atayoğlu, Ali Timuçin; Galeotti, Fabio; Garzarella, Emanuele U.; Zaccaria, Vincenzo; Volpi, Nicola; Karagöz, Ali; Şahin, Fikrettin (International Medical Press Ltd, 2021)
Background: Viral infections are among the most common problems in health-care practice. Natural products offer great promise as potentially effective antiviral drugs. Propolis is a honeybee product with biological properties and therapeutic applications. We aimed to investigate the antiviral activity of different extracts of Standardized Propolis Preparations (M.E.D.(R)) with glycol, ethanol, glycerol and soya oil, against herpes simplex type-1 (HSV-1) and type 2 (HSV-2) viruses. Methods: Chemical composition and antiviral activity of each extract were determined. The selective index (SI=CC50/EC50) was determined as a parameter to indicate the in vitro antiviral activity of the extracts compared with acyclovir as the control. Results: SI values of glycol, ethanol, glycerol, soya oil extracts and acyclovir were determined as 6.8, 4.1, 2.2, 3.3 and 6.3 against HSV-1, and as 6.4, 7.7, 1.9, 4.2 and 2.9 against HSV-2, respectively. Glycolic propolis extract was found to possess a greater antiviral activity than acyclovir for both HSV-1 and 2, while glycolic, ethanolic and soya oil preparations were found to have more significant activity than acyclovir for HSV-2. Conclusions: It was determined that standardized propolis preparations have antiviral bioactivity against HSV.
Keywords: HSV; Preparations Against; Standardized Propolis